2022
DOI: 10.1186/s12888-022-04476-z
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility and acceptability of a task-shifted intervention for perinatal depression among women living with HIV in Malawi: a qualitative analysis

Abstract: Background Perinatal depression (PND) is prevalent and negatively impacts HIV care among women living with HIV (WLHIV), yet PND remains under-identified in Malawian WLHIV. Accordingly, this formative study explored perceptions of the feasibility and acceptability of an integrated, task-shifted approach to PND screening and treatment in maternity clinics. Methods We completed consecutive PND screenings of HIV+ women attending pre- or post-natal appo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Some women in our study reported that group counseling might foster strong communication while others expressed concerns surrounding privacy, especially if the counselor were a member of her community. This is consistent with a qualitative study among women with perinatal depression in Malawi in which participants preferred individual to group therapy [24,25]. Future studies should nonetheless evaluate the acceptability of group IPT in Lusaka, as studies in Tanzania and Kenya have shown group therapy to be both feasible and acceptable among women with HIV and depression [26,27].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Some women in our study reported that group counseling might foster strong communication while others expressed concerns surrounding privacy, especially if the counselor were a member of her community. This is consistent with a qualitative study among women with perinatal depression in Malawi in which participants preferred individual to group therapy [24,25]. Future studies should nonetheless evaluate the acceptability of group IPT in Lusaka, as studies in Tanzania and Kenya have shown group therapy to be both feasible and acceptable among women with HIV and depression [26,27].…”
Section: Discussionsupporting
confidence: 81%
“…Studies on the acceptability of ADM treatment for depression among adults with HIV in SSA differ in their findings. Some report medication-based treatment is acceptable to patients, while others report challenges with medication-based therapy in low-resource settings, including limited knowledge of medication-based treatments for depression among patients and providers, challenges with reliably accessing medications, and a preference for psychosocial interventions [25,[30][31][32]. This study provided participants with medications, and we suspect the same barriers to access are present in Zambia.…”
Section: Discussionmentioning
confidence: 92%
“…Task-shifting is an implementation strategy focused on training non-specialists to deliver specialized services like prescribing antidepressant medication or providing psychosocial counseling ( Galvin and Byansi, 2020 ; Johns et al, 2018 ). In Malawi, task shifting efforts have proven feasible in integrating depression screening, psychosocial counseling, and anti-depressant medication prescription into routine HIV and perinatal care, but have been further hindered by lack of intervention fidelity and sustainability ( Kulisewa et al, 2022 ; Stockton et al, 2020 ; Udedi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…(either due to material resources, transit access, or work/scheduling), and stressful life events (e.g., a dispute with a partner or family member) as key determinants to attending their care appointments [14][15][16]. Research in other social contexts has also demonstrated that suboptimal treatment engagement may reduce the effectiveness of depression treatment and increase time to depression remission [7].…”
Section: Introductionmentioning
confidence: 99%